Impact of rate control medications on one-year outcomes with atrial fibrillation and heart failure. (14th October 2021) - Mo, R; Yang, Y; Yu, L
Abstract: Purpose: Atrial fibrillation (AF) and heart failure (HF) often coexist. The impact of rate-control regimens in AF and HF patients has not been well understood. Methods: In this multicenter, prospective registry with one-year follow-up, 1359 persistent or permanent AF patients got enrolled. A 1:1 HF to non-HF propensity score matching was applied to adjust for confounding variables. The primary endpoint was all-cause mortality while the secondary endpoint was defined as cardiovascular death and stroke. Multivariate Cox analysis was performed to evaluate the association between different rate-control treatment and incidence of adverse events. Results: Before matching, HF patients were much younger and more likely to be female. They had a much higher prevalence of previous myocardial infarction, chronic obstructive pulmonary disease and valvular heart disease. Among 1359 participants, we identified 1016 matched patients. The number of drugs did not affect the risk of all-cause mortality in both cohorts. For non-HF patients, using calcium channel blockers (CCBs) plus digoxin had a significant higher risk of all-cause death (HR=5.703, 95% CI 1.334–24.604, p=0.019) and cardiovascular death (HR=9.558, 95% CI 2.127–42.935, p=0.003) compared with patients not receiving rate-control treatment. The use of beta-blockers, CCBs, digoxin alone, other dual or triple combinations was not related to risk of adverse events in both groups. Conclusions: The combined use of CCBs and digoxin was related to increase all-cause and cardiovascular mortality in AF patients without HF but not for those with HF. However, the ideal rate-control regimen for AF and HF patients has not been established and well-designed clinical trials are needed. Funding Acknowledgement: Type of funding sources: None.